2018
DOI: 10.3390/catal8010025
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Nanotubes on Transparent Substrates: Control of Film Microstructure and Photoelectrochemical Water Splitting Performance

Abstract: Abstract:Transfer of semiconductor thin films on transparent and or flexible substrates is a highly desirable process to enable photonic, catalytic, and sensing technologies. A promising approach to fabricate nanostructured TiO 2 films on transparent substrates is self-ordering by anodizing of thin metal films on fluorine-doped tin oxide (FTO). Here, we report pulsed direct current (DC) magnetron sputtering for the deposition of titanium thin films on conductive glass substrates at temperatures ranging from ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 44 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…A promising approach to fabricate nanostructured TiO 2 films on transparent substrates is self-ordering by the anodizing of thin metal films on fluorine-doped tin oxide (FTO) coupling pulsed direct current (DC) magnetron sputtering for the deposition of titanium thin films on conductive glass substrates and anodization and annealing for the TiO 2 nanotube array [13]. Zelny et al reported a detailed investigation of mechanical and adhesion properties of Ti films sputtered at different temperatures, showing that a more active TiO 2 nanotube sample towards photoelectrochemical water splitting was obtained from a Ti substrate sputtered at 150 • C, showing the lowest crystallite size, best degree of self-organization, and enhanced charge transfer at the semiconductor/liquid interface.…”
Section: This Special Issuementioning
confidence: 99%
“…A promising approach to fabricate nanostructured TiO 2 films on transparent substrates is self-ordering by the anodizing of thin metal films on fluorine-doped tin oxide (FTO) coupling pulsed direct current (DC) magnetron sputtering for the deposition of titanium thin films on conductive glass substrates and anodization and annealing for the TiO 2 nanotube array [13]. Zelny et al reported a detailed investigation of mechanical and adhesion properties of Ti films sputtered at different temperatures, showing that a more active TiO 2 nanotube sample towards photoelectrochemical water splitting was obtained from a Ti substrate sputtered at 150 • C, showing the lowest crystallite size, best degree of self-organization, and enhanced charge transfer at the semiconductor/liquid interface.…”
Section: This Special Issuementioning
confidence: 99%
“…The existence of several concerns related to the increasing energy demand and the related environmental crisis [1][2][3][4][5][6] indicates the need to identify innovative, effective and low cost solutions. Photoelectrochemical water splitting (PWS) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] is recognised as a promising strategy and it attracts particular interest for storing solar energy into the chemical bonds of hydrogen as fuel [26][27][28], which can be further utilised in fuel cells [29][30][31][32][33][34], internal combustion engines and to progressively decarbonize industrial processes [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Constructively, our cost effective photocatalyst 50TNT-50GO has shown superior photoelectrocatalytic water splitting performances (9.2 mA cm -2 ) compared to others in literatures such as various black titania either produced via reduction by CaH 2 (1.99 mA cm -2 ) or Mg metal (3.1 mA cm -2 ) [19][20]. It also exceeds those of the ternary structured Ag/TiO 2 /CNT (0.9 mA cm -2 ), TiO 2 @RG (6.0 mA cm -2 ), reduced graphenegraphene oxide nanohybrid (61.35 μA/cm 2 ) and controlled lm of TiO 2 nanotubes (175 µA cm −2 ) [21][22][23][24] all performed in the same electrolyte.…”
Section: Photoelectrochemical Water Splittingmentioning
confidence: 93%